MICROECONOMIC FOUNDATIONS OF MARKET EQUILIBRIUM AND PRICE FORMATION: ANALYSIS BASED ON THE EXAMPLE OF THE UZBEK ECONOMY - Shukurova Khayriniso Zokir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article provides a theoretical and practical analysis of core microeconomic concepts such as demand and supply equilibrium, price mechanism, and resource allocation. Factors influencing the formation of market equilibrium in Uzbekistan, and how consumer and producer decisions are coordinated through market prices, are examined. The article also offers recommendations for increasing market efficiency through the preservation of microeconomic equilibrium.